READINESS TO LEARN: PRINCIPLES. CONTRIBUTING FACTORS AND HOW IT AFFECTS LEARNING - Agustiani, Indah Windra Dwie; Gumartifa, Asti Gumartifa; Yaman, Herasni Yaman (Universitas Muhammadiyah Palembang, 2021)
This study attempts to inform definition of learning readiness, the principle of readiness, factors contributing to readiness to learn and how readiness affects learning. This study is theory-based research or library research.This study used secondary data. The technique used for collecting the data is literature study. This study concludes that the principles of readiness are not only affected by one’s physical development but also his/ her mental development since they are closely interrelated. Moreover, the suitability of the learning experiences that will be given or the existing (prior) experiences become crucial to result in learning readiness and simultaneously , and the adaptation process of basic readiness for certain activities is considered as a natural thing when it is in the formation period at the time of development .Factors contributing to readiness to learn are maturation ,Intelligence, and motivation and readiness can generate active self directed learner, improve learning outcome/achievements.grow responsibility in learning ,and influence students’ activeness in learning.